Processos de trabalho no telejornalismo da TV Sergipe : impactos da pandemia de COVID-19 - Cardoso, Anna Paula Correia Ferreira e (2023)
This research seeks to record, analyze and understand the journalistic practices used by television journalism with the Coronavirus pandemic. With the advancement of contamination and the imposition of sanitary rules aimed at distancing and consequent control of contamination, new journalistic routines were established. The way of doing journalism, as it was conceived until then, went through a restructuring in a circumstantial way, singularly altering the telejournalistic praxis, being in the first two years marked by a movement of rupture in the productive processes to give way to the return of practices adopted before the covid-19. This research follows the previous scenario, during and after it (between 2019 and 2022 and reflects on the influences of the pandemic for a post-virus newsroom, with the transformations that were rooted or not. Based on these reflections, we seek to answer the following questions Questions: What changes are consequences of the pandemic? Was there a break in aspects of the journalistic routine? Which aspects maintained continuity? What changes occurred circumstantially and returned to previous patterns? What changes introduced innovations in the work process of telejournalism? We maintain as hypotheses that the processes of journalistic convergence based on technology significantly influenced the productive routines of the television news and the pandemic also generated a change in production routines with the division between street work and home work of the team, with an intensification of the pace and volume of work and shift flexibility. We consider aspects such as the use of information technology, the mutability of news and structural transformations. The empirical clipping given is for the daily news program Bom Dia Sergipe, on Tv Sergipe, an affiliate of Tv Globo in Sergipe, in a period prior to, during and close to the end of the public health emergency decreed by the World Health Organization. in the case study methodology and in the Theory of Newsmaking, understanding the news from the social construction of facts, production routines and journalistic organization. We also corroborate with works on pandemic coverage, by authors such as Emerim et al. (2020), Belém et al (2020), Monteiro and Siqueira (2020), Paulino et al (2020).